13th International Conference on Interactive Computer aided Learning - ICL2010 - for Papers, Call (International Journal of Advanced Corporate Learning (iJAC), 2010)
This interdisciplinary conference aims to focus on the exchange of relevant trends and research results as well as the presentation of practical experiences in interactive computer aided learning, in higher education and in corporate context, and seen in a global context. The conference will be organized by the University of Hasselt, Belgium.